Synthetic Aperture Orbital Telescope for Earth Remote Sensing Equipment - D. A. Kozhevnikov; R. V. Fiodоrtsev; A. r Silie (Приборы и методы измерений)
The object of the research is the development of the method of aperture synthesis of a mirror system designed for remote sensing of the Earth.The analysis of existing methods for the formation of the synthesized aperture was carried out, their accuracy, cost, and mass-dimensional characteristics were evaluated. A new version of the optical system of the synthetic aperture mirror lens is presented and its optimization is performed in the Zemax software package. An estimate of the accuracy of the designed system has been made; a design variant has been developed that includes a transformation mechanism when the telescope is put into near-earth orbit.As a result of the study, the design parameters of the base lens were determined: a focal length of 13 m, a main mirror diameter of 800 mm, a field angle of 0.25° for modifying a telescope for a low orbit; and the entire telescope as a whole: the lag from the main axis of the telescope is 1.2 m, the angle of rotation of the flat mirror for combining images (45 + 1,5)°, the signal-to-noise ratio (189 in a low orbit with an angle of the Sun 0°, 15 in the geostationary orbit with a sun angle of 60°).It has been established that the use of aperture synthesis technology allows the development of highresolution optical-electronic systems with lower production and operation costs compared with classical methods for forming the surface of the main mirror. In the course of the simulation, the instability of the values of the frequency-contrast characteristic with increasing angle of view was determined, which is important for a low near-earth orbit, and the requirement for positioning elements of the optical system was established.